My favorite holidate : a novel - Blakely, Lauren (Atria Books, 2025)
"Wanted: hot billionaire to pose as my Christmas boyfriend. Must be willing to make my cheating ex jealous by kissing me under the mistletoe at holiday parties. Bonus if you make him cry." To Fable's surprise, her billionaire boss, Wilder Blaine, is more than willing to take on the challenge of playing her holiday boyfriend. The sexy single dad desperately needs a plus one for a Christmas Eve wedding, where he's the best man and she's the maid of honor. With her ex also in the wedding party, the two team up as a pair of insta-lovebirds for the holiday season. Their partnership includes participating in the annual week-long Christmas competition leading up to the snowy destination wedding.